PERILAKU TRASH-TALKING PADA GAME ONLINE MOBILE LEGENDS: (Etnografi Virtual pada Player Mobile Legends: Bang Bang) - Zahwa Alrizky; Muhammad Ramdhani; Weni A. Arindawati (Journal Publicuho, 2025)
This study examines the phenomenon of trash talking in the online game MLBB using a virtual ethnography approach. Trashtalking, which is characterized by the use of negative or provocative verbal communication, is analyzed as a response to competitive pressure, community norms, anonymity in the digital world, and spontaneous emotional reactions. This study uses a qualitative descriptive method with a Virtual Ethnography approach. Based on the results of the study, it can be concluded that the Trash-talking phenomenon in Mobile Legends: Bang Bang is influenced by various factors and has a significant impact, both psychologically, socially, and culturally in the player community. The main factors that drive this behaviour include competitive pressure in-game dynamics, culture and community norms that consider Trash-talking as part of the gaming experience, the influence of anonymity that blurs real-world social boundaries, spontaneous responses to intense emotions during the game, and psychological strategies to influence opponents or raise team spirit. The virtual ethnography approach reveals that the digital world, especially in the context of online games, reflects various aspects of more complex human social interactions, including conflict, solidarity, and emotional expression. The impact of Trash-talking behaviour covers various aspects. From a psychological perspective, Trash-talking can increase stress and anxiety in certain players, but it can also build mental resilience in individuals who manage the pressure.